Sexualité juvénile et fabrique du genre en milieu rural en Suisse - Alexandre Dafflon (Genre, Sexualité et Société)
The sexuality of youth has rarely been studied in situ, allowing for various interpretations of how this is expressed in terms of gender. Based on an ethnographic investigation of members of rural youth groups in the French-speaking part of Switzerland, this article intends to demonstrate how sexual experiences there reveal a great deal about the establishment of gender relationships. Structured around the primacy of the heterosexual norm, they push young people to identify with one sex and to internalize the forms associated with it socially. For boys, these would be sexual exuberance and the exercise of domination, and for girls, modesty and displaying of feelings. Yet individuals also deploy various strategies when faced with these normative injunctions, and play with the principles with which they are confronted. This is particularly evident for those whose sexuality fails to correspond to what is expected of their sex. Thus, the article focuses on investigating the way in which young people respond to the norms to which they are subjected, and the extent to which they manage to either confirm or redefine the established hierarchies.